2014
DOI: 10.1177/0194599814545750
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Sinonasal Outcomes of Aspirin Desensitization in Aspirin Exacerbated Respiratory Disease

Abstract: Aspirin desensitization following ESS appears to be a well-tolerated and effective adjunctive therapy for long-term control of nasal polyposis in patients with AERD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
101
0
5

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(115 citation statements)
references
References 29 publications
9
101
0
5
Order By: Relevance
“…10 Los beneficios demostrados con la desensibilización a la aspirina incluyen la reducción de: síntomas de rinosinusitis crónica, número de intervenciones quirúrgicas debidas a la poliposis nasal, gravedad del asma, con dosis de 650 mg cada 12 h. Algunos pacientes también muestran estas ventajas con dosis de 325 mg cada 12 h, en menor proporción se exacacerban al reducir la dosis, la que debe incrementarse nuevamente. 11 La principal causa de abandono del tratamiento es la toxicidad gastrointestinal asociada con la ingesta de ácido acetilsalicílico, por lo que se recomienda la prescripción concomitante de protectores de la mucosa gástrica. 11 La enfermedad respiratoria exacerbada por aspirina afecta la calidad de vida de los pacientes y genera un alto costo del tratamiento farmacológico y quirúrgico; por esto se sugiere evaluar la utilidad del protocolo de desensibilización al ácido acetilsalicílico.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…10 Los beneficios demostrados con la desensibilización a la aspirina incluyen la reducción de: síntomas de rinosinusitis crónica, número de intervenciones quirúrgicas debidas a la poliposis nasal, gravedad del asma, con dosis de 650 mg cada 12 h. Algunos pacientes también muestran estas ventajas con dosis de 325 mg cada 12 h, en menor proporción se exacacerban al reducir la dosis, la que debe incrementarse nuevamente. 11 La principal causa de abandono del tratamiento es la toxicidad gastrointestinal asociada con la ingesta de ácido acetilsalicílico, por lo que se recomienda la prescripción concomitante de protectores de la mucosa gástrica. 11 La enfermedad respiratoria exacerbada por aspirina afecta la calidad de vida de los pacientes y genera un alto costo del tratamiento farmacológico y quirúrgico; por esto se sugiere evaluar la utilidad del protocolo de desensibilización al ácido acetilsalicílico.…”
Section: Discussionunclassified
“…11 La principal causa de abandono del tratamiento es la toxicidad gastrointestinal asociada con la ingesta de ácido acetilsalicílico, por lo que se recomienda la prescripción concomitante de protectores de la mucosa gástrica. 11 La enfermedad respiratoria exacerbada por aspirina afecta la calidad de vida de los pacientes y genera un alto costo del tratamiento farmacológico y quirúrgico; por esto se sugiere evaluar la utilidad del protocolo de desensibilización al ácido acetilsalicílico.…”
Section: Discussionunclassified
“…Many studies have shown that AD followed by daily aspirin treatment was associated with an improved clinical course in patients with AERD [8,[19][20][21][22][23][24][25][26][27][28][29][30][31][32] . A wide of aspirin dosages (100-1,300 mg/day) were used for the purpose of AD in these studies.…”
Section: Clinical Trials Of Admentioning
confidence: 99%
“…A wide of aspirin dosages (100-1,300 mg/day) were used for the purpose of AD in these studies. There was varying degree of clinical benefit obtained from AD in different studies; some showing benefit for only control of upper airway disease [8,[20][21][22] and some for both upper and lower airway disease [19,[23][24][25][26][27][28][29][30][31][32] . To our knowledge, in only one study, which was carried out on 10 aspirin sensitive asthma patients by using 500 mg aspirin, AD was found ineffective as measured as an improvement on pulmonary function tests and reduced need for systemic corticosteroids [33] .…”
Section: Clinical Trials Of Admentioning
confidence: 99%
See 1 more Smart Citation